(untitled) (Fiep Bulletin - online, 2024)
Objective: To analyze the consequences of the Covid-19 pandemic on the body composition and mental health of physical education teachers in the city of João Pessoa. Methods: This is a cross-sectional descriptive study, in which a questionnaire was applied to 114 (48.3%) Physical Education teachers from the municipal network of João Pessoa. In this questionnaire there were questions about sociodemographic characteristics, body composition, physical and psychological health before and during the pandemic. For the quantitative data, the wilcoxon test was used, while for the qualitative data of the questionnaire, they were presented through descriptive statistics of frequency distribution. Results: It was observed that there was a higher relative frequency for men (56.1%), aged between 31 and 40 years old (40.4%), with 60.5% being married. As for physical and psychological health, there was a higher relative frequency of stress during the pandemic with an increase in the exhaustion phase (8.8%). As for health before and during the pandemic, there was the appearance of a classification that did not exist before the pandemic, which was the terrible classification (8.8%). In the comparative analysis of body mass and body mass index of all teachers, it was observed that there was a significant difference between before and during the pandemic (p=0.010; p=0.008), respectively. Teachers who did not have covid-19 significantly increased their body mass and body mass index (p=0.009, p=0.008), respectively. Conclusion: There was an increase in body composition and mental health of Physical Education teachers in the city of João Pessoa.